Effectiveness of Oxytocin Massage Combination Jamu Bejja on Breast Milk Production and Uterine Involution - Feftin Hendriyani; Suryaningsih Suryaningsih (Alliance oh Health Activists (AloHA), 2024)
Introduction: A breastfeeding mother has many nutritional needs in every food she consumes by paying attention to the needs needed by her body. Breast milk is a liquid to meet the nutritional needs of babies and protect from disease. Breast milk is given to babies because it can prevent infectious and non-communicable diseases, as well as increase IQ, EQ, and strengthen the affectionate relationship between mother and child. The World Health Organization (WHO) recommends that every newborn should be exclusively breastfed for six months. However, exclusive breastfeeding is a program that is quite difficult to develop. The cause of the low level of exclusive breastfeeding stems from the delay in breastfeeding which resulted in a decrease in breast milk production. This study aimed to determine the effectiveness of the Combination of Jamu Bejja and Oxytocn Massage on Breast Production and Uterine Involution. Methods: The design used a quasi-experiment. The population was postpartum mothers in Bangkalan Regency. The sample consisted of 30 in treatment groups 1, 30 in treatment groupt 2 and 30 in control groups. The variables were oxytocin massage, jamu bejja, milk production and uterine involution. Data collection used observation sheets (quasi-experimental). Data analysis used man whitney and kruskal wall tests. Results: there were differences in the effect of the combination of oxytocin massage and jamu bejja Madura on milk production and uterine involution with α